(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
COVID-19 and its causative agent primarily affects the lung tissues and disrupts gas exchange, which leads to acute respiratory distress syndrome, systemic hypoxia and lung damage. It is known that the COVID-19 virus needs certain conditions from the cell membranes to penetrate into the lung or intestinal cells: the presence of structures that allow the virus to «catch on» to the cell (ACE2 receptor), the TMPRSS2 protein structure. The TMPRSS2 enzyme activates Coronaviruses such as SARS-CoV and SARS-CoV-2 and, therefore, inhibitors of this enzyme can block the virus. The virus uses APF2 as a receptor for entering the cell, and TMPRSS2 is necessary for the activation of the viral S-protein. Without these structures, the penetration of the COVID-19 virus into the cell is impossible. It was found that activation of the HIF-1 α-signaling pathway under conditions of moderate hypoxia will reduce ACE2 and TMPRSS2 and increase ADAM17 levels on the surface of alveolocytes and, consequently, reduce the invasiveness of SARS-CoV-2.